2007
DOI: 10.1002/mrdd.20149
|View full text |Cite
|
Sign up to set email alerts
|

Translating policy principles into practice to improve health care access for adults with intellectual disabilities: A research review of the past decade

Abstract: This article extracts principles from two Surgeon General reports, Closing the Gap: A National Blueprint to Improve the Health of Persons with Mental Retardation (2002) and Call to Action to Improve the Health and Wellness of Persons with Disabilities (2005), and combines them with the Objectives from Chapter 6 of Healthy People 2010 to create a policy framework. This framework is used to review literature from the past decade on access to health care and health promotion for persons with intellectual and deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 80 publications
0
30
0
Order By: Relevance
“…Consequently, we need to focus attention on resources that provide both formal and informal services that can support a quality of life to “age in place,” as individuals with I/DD are aging and will outlive family caregivers, creating uncertainty for future care giving, health care, and housing needs. Families are struggling to find adequate lifelong care and services, especially those that enhance or support quality of life needs [10, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we need to focus attention on resources that provide both formal and informal services that can support a quality of life to “age in place,” as individuals with I/DD are aging and will outlive family caregivers, creating uncertainty for future care giving, health care, and housing needs. Families are struggling to find adequate lifelong care and services, especially those that enhance or support quality of life needs [10, 30]. …”
Section: Discussionmentioning
confidence: 99%
“…Very few workers or consumers reported being exploited and the fraudulent use of the cash benefit was extremely rare (Schore et al, 2007). The Arkansas C & C evaluation team has found that participation in the program resulted in good health outcomes (Krahn & Drum, 2007;Simon-Rusinowitz, Mahoney, Loughlin, & Sadler, 2005).…”
Section: Effectivenessmentioning
confidence: 97%
“…There is a dearth of US studies on programs to improve clinician training on ID, 8 and the modest extant literature regarding clinician preparation indicates inadequate or absence of formal training on ID. 9 Currently, there is no curriculum requirement for US medical schools specifically to teach competency in the provision of care to persons with ID. Not surprisingly, many physicians are ill prepared to recognize symptoms or appropriately examine patients who have the physical limitations, communication difficulties, or behavioral issues that often coexist in persons with ID.…”
Section: T He Population Of Older Adults In the Unitedmentioning
confidence: 99%